Secure communication scheme using chaotic time-varying delayed system. (7th June 2019) - Benkouider, Khaled; Halimi, Meriem; Bouden, Toufik
In this paper, we are interested in the study of discrete-time delayed chaotic communication system where the delay is injected into the state vector of the chaotic system in order to increase the security of the transmission. Our aim is reconstructing the encrypted information at the receiver. However, this reconstruction requires knowing the delay. We propose a method based on the use of unknown input polytopic observers, to estimate the unknown delay and the encrypted information. The obtained simulation results show the effectiveness of this method.